2014
DOI: 10.4049/jimmunol.1301893
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin Induces Antibody Responses through a TLR5- and Inflammasome-Independent Pathway

Abstract: Flagellin is a potent immunogen that activates the innate immune system via TLR5 and Naip5/6, and generates strong T and B cell responses. The adaptor protein MyD88 is critical for signaling by TLR5, as well as IL-1 and IL-18 receptors, major downstream mediators of the Naip5/6 Nlrc4-inflammasome. Herein we define roles of known flagellin receptors and MyD88 in antibody responses generated towards flagellin. We used mice genetically deficient in flagellin recognition pathways to characterize innate immune comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 93 publications
(128 reference statements)
6
86
0
Order By: Relevance
“…(Figure 2a). This suggests that TLR5-stimulating activity was important for activating the antibody response against flagellin, as observed previously, 32 whereas the NLRC4-stimulating activity contributed much less to the antibody response against flagellin. Interestingly and surprisingly, FliC-L3A induced a significantly higher IgG response than did FliC (Figure 2a).…”
Section: Preparation Of Flagellins and Verification Of Their Tlr5-andsupporting
confidence: 55%
See 4 more Smart Citations
“…(Figure 2a). This suggests that TLR5-stimulating activity was important for activating the antibody response against flagellin, as observed previously, 32 whereas the NLRC4-stimulating activity contributed much less to the antibody response against flagellin. Interestingly and surprisingly, FliC-L3A induced a significantly higher IgG response than did FliC (Figure 2a).…”
Section: Preparation Of Flagellins and Verification Of Their Tlr5-andsupporting
confidence: 55%
“…18 Ló pez-Yglesias et al found that the deletion of Naip5 in mice did not change the number of IgG1 anti-FliC antibodies using Naip5 KO mice. 32 However, flagellin-immunized A/J MyD88 2/2 mice (natural partially defective in Naip5) induced higher IgG1 and IgG2a responses against flagellin than did C57BL/6 mice. 32 Nordlander et al found that NLRC4 KO mice mounted a stronger specific humoral response compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations